AVALIAÇÃO DA QUALIDADE DE PRESUNTO COZIDO E INFLUÊNCIA DO EMPREGO DE MATÉRIA-PRIMA CONGELADA - Los, Francine Gomes Basso (2014)
Meat products’ consumption in Brazil is still low considering the favorable condition of largest exporter of meat in the world. With the increase of income of the population that scenario tends to change with additional consumption. Studies on the quality of products sold in the domestic market need to be constantly conducted in order to assist the high quality and safety of products providing and, as well, new technology and concepts need to be studied to increase the demand for products. Despite the consensus that the freezing of meat affects its functional properties, several studies have been conducted to evaluate its use in processed meat products, in order to increase the availability of raw materials and flexibility of industries. In this context, the objectives of this work were study the quality of cooked hams sold in the domestic market and to classify them by means of multivariate analysis, and study the influence of freezing of raw material and the use of exudate released upon thawing, on cooked ham’s production. To study the quality of cooked hams eleven commercial samples were evaluated for microbiological quality, physico-chemical and rheological, and studied by means of Hierarchical Cluster Analysis (HCA) and Principal Component Analysis (PCA). Regarding to legal standards, eight samples were in accordance with all parameters required by the law, two samples were fraud by the addition of starch, and one sample showed sodium content above stated on the label. The samples were classified by HCA in three groups of distinct quality, with a significant difference in moisture content, chromaticity, losses of syneresis, heating and freezing. Analyzing the results of the sensorial analysis applied and instrumental parameters was possible, by applying PCA, demonstrate that samples more accepted by consumers in relation to flavor and overall acceptability were the samples that showed higher levels of moisture, protein, fat and luminosity. To study the influence of freezing of raw material in cooked ham, pork leg was frozen by slow (-18 º C) and fast method (liquid nitrogen) and maintained for 22 weeks in storage at -18 ° C. After this period the meat samples were thawed and the exudate was collected. Cooked hams were produced with the raw material frozen/thawed by both methods, with and without using exudate. A control sample, with fresh raw material was also produced. Samples of hams were analyzed for physico-chemical, structural (rheological and histological), technological and sensory characteristics. The samples showed no significant difference regarding to the physicochemical, color and sensory analyzes. Statistical difference was observed in hardness and chewiness. Histological analysis showed changes in the tissues caused by the freezing and thawing of raw materials. The effect of increasing exudate was significant only for compression force and sodium content, but still, this difference was not perceived by sensory analyzes. This result indicates the possibility of using frozen meat, under the conditions tested, for cooked ham, which may be interesting from an industrial point of view to increase the flexibility of the processing plants due to the great availability of this type of raw material. This study demonstrated that multivariate techniques were effective in assessing the quality of cooked hams and proved the possibility of using raw frozen this type of product, according to the tested conditions, which may be interesting from an industrial point of view to increase the flexibility of processing plants due to the large availability of such raw materials.